2022
DOI: 10.3389/fnhum.2021.762492
|View full text |Cite
|
Sign up to set email alerts
|

Notched Sound Alleviates Tinnitus by Reorganization Emotional Center

Abstract: BackgroundTinnitus is a common disease, and sound therapy is an effective method to alleviate it. Previous studies have shown that notched sound not only changes levels of cortical blood oxygen, but affects blood oxygen in specific cerebral cortical areas, such as Brodmann area 46 (BA46), which is associated with emotion. Extensive evidence has confirmed that tinnitus is closely related to emotion. Whether notched sound plays a role in regulating the emotional center is still unclear.MethodsThis study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
1
Order By: Relevance
“…Several scholars have found that BA46 is a key node in the cognitive control network that supports working memory [41]. BA46 is thought to be involved in cognitive and behavioural tasks related to emotional behaviour and affect regulation [42], and the importance and urgency of turn manoeuvres may trigger pilots' emotional responses. In summary, the results of this study suggest that the different steering behaviours of pilots are mainly related to BA17, BA18 and BA46.…”
Section: A Statistical Analysis Resultsmentioning
confidence: 99%
“…Several scholars have found that BA46 is a key node in the cognitive control network that supports working memory [41]. BA46 is thought to be involved in cognitive and behavioural tasks related to emotional behaviour and affect regulation [42], and the importance and urgency of turn manoeuvres may trigger pilots' emotional responses. In summary, the results of this study suggest that the different steering behaviours of pilots are mainly related to BA17, BA18 and BA46.…”
Section: A Statistical Analysis Resultsmentioning
confidence: 99%
“…Currently, the number of sensors used is relatively small, so that a priori decisions must be made as to which regions’ activity will be recorded and evaluated. Initial studies indicate that cortical changes in tinnitus are not limited to auditory regions 55 , but also affect emotion-relevant regions 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Erste Untersuchungen weisen auch hier daraufhin, dass sich kortikale Veränderungen bei Tinnitus nicht auf auditive Regionen beschränken 55 , sondern auch hier z. B. emotionsrelevante Regionen betreffen 56 .…”
Section: Schlussfolgerungen Und Ausblickunclassified
“…The other study (Huang et al, 2021) used fNIRS to assessed changes in resting cortical function before and after 1-month notched sound treatment in 21 tinnitus patients. Results indicate that notched sound treatment induced stable cortical reorganization.…”
Section: Sound Therapymentioning
confidence: 99%